The effect of vitamin A supplementation on morbidity due to Plasmodium falciparum - Adillida Adillida; Yoyoh Yusroh; Munar Lubis; Bidasari Lubis; Tiangsa Sembiring; Syahril Pasaribu (Indonesian Pediatric Society, 2004)
Objective To investigate the effect of vitamin A supplementationon malaria morbidity.Methods The study was a randomized double-blind placebo-con-trolled trial, conducted in Panyabungan, Mandailing Natal, NorthSumatera from April 2001 to April 2002. Children aged 6-60 monthssuffering from falciparum malaria were randomly assigned to highdose vitamin A or placebo every 4 months for a year. All childrenwere treated in accordance with health center policy. Malaria mor-bidity was assessed from health center visit due to fever, diarrhea,cough, or abdominal pain. Parents gave reports if their child re-ceived malaria treatment from other health centers.Results The number of febrile episodes (probable malaria illness)was lower in the treatment group than that of control, but not sig-nificant. The parasitemia was not different between both groups.There was a significant difference in spleen enlargement betweenthe treatment group and control (p=0.04). There was no differencein health center visit between the two groups.Conclusion The findings suggest that vitamin A supplementationhas only effect on spleen enlargement in malaria.